Influence of Urban Underground Spiral Ramp Curve Design on Vehicle Running Performance - ZHENG, Liwei; YANG, Libo; ZHENG, Zhanji; WANG, Yanpeng; XU, Jin (Promet - Traffic&Transportation, 2026)
Urban underground spiral ramps’ continuous curves and the monotonous tunnel environment increase driving safety risks and reduce vehicle stability. To clarify the influence of road geometric alignment parameters on vehicle acceleration in urban underground spiral ramp curves, a real vehicle test was conducted on the Jiefangbei Underground Ring Road - Hongyamen Underground Road in Yuzhong District, Chongqing, China. On-board instruments collected acceleration data from 20 drivers to analyse how curve radius and angle affect the vehicle’s three-axis acceleration. The results show that: (1) The exit acceleration of the spiral ramp curve is positively correlated with the curve radius and negatively correlated with the turning angle, while entrance deceleration exhibits the opposite trend. (2) Lateral acceleration is negatively correlated with curve radius but positively correlated with turning angle. (3) Vertical acceleration increases with curve radius on upward curves and decreases on downward ones; the opposite occurs with turning angle. (4) Vehicle acceleration differs significantly under varying radii and turning angles. The average exit acceleration is higher for ordinary-radius (or small turning angle) curves than for small-radius (or large turning angle) curves, while the average lateral acceleration exhibits the opposite trend. These findings reveal passenger car driving behaviour characteristics on urban underground spiral ramps, supporting future curve geometric design and safety studies.